ANALYSIS OF SUSTAINABILITY FARMING IN PEATLANDS IN BATAGUH SUB DISTRICT, KAPUAS DISTRICT - Jhon Wardie; Tri Yuliana Eka Sintha (Agros Journal of Agriculture Science, 2017)
The research aims to analize: (1) level of sustainability farming of rice in peat land and (2) level of farmers household income in peat land. Research location determined by purposive sampling in Terusan Karya Village, Bataguh Sub District, Kapuas. Sampling was done by simple random sampling method by taking 50 farmers household serve as respondent. Data collected in form of primary and secondary data. To achieve the purpose of first study were analyzed by scoring sustainability of farming indicators using Likert Scale system. Indicator of farming sustainability is an instrument that includes biophysical and socio-economic aspects used to measure the level of sustainability of farming of rice in peat land. To achieve purpose of second study analyzed a simple tabulation to measure level of farmers household income. Based on analysis of farming sustainability of rice in peat land turns farming sustainability index by 76.10 percent, which means that the level of farming sustainability is good category (highly sustainable). The results of the analysis of farmers household income was found that the level of farmer households income of IDR 16,906,614 which means that the economic situation has been categorized good farmer households.